PROBLEMATIC RECOMMENDATIONS FOR TRANSLATING NATIONAL-CULTURAL SEMANTICALLY MARKED LEXICAL UNITS IN UZBEK AND ENGLISH LANGUAGES (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article analyzes the current challenges in translating national-cultural semantically marked lexical units between Uzbek and English. It explores the semantic, linguistic, and pragmatic difficulties that arise when attempting to render culturally and socially rooted expressions from one language into another. These lexical units are often deeply connected to a nation’s lifestyle, traditions, and worldview, which makes direct translation inadequate or misleading. Therefore, the paper offers recommendations on alternative translation strategies, such as using functional equivalents, descriptive translation, and enhancing intercultural competence. Through practical examples, the study illustrates the issues encountered in translating Uzbek expressions into English and discusses possible solutions to convey their cultural connotations effectively. The research provides both theoretical insight and practical guidance for translators working in bilingual and cross-cultural contexts, contributing to a more accurate and culturally sensitive translation practice.